INVESTIGATION INTO PITFALLS ENCOUNTERED WHILE TRANSLATING “LINKEDIN” ARTICLES - Gemma Navickienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Translatology is based on the study of the theory and practice of translating, especially in an academic context, which calls for research into the practice of translation and insights on how to teach it emphasising the importance of adapting the translation theory and accommodating it to the needs of the classroom.. The research aims to identify the pitfalls encountered by students in the field of translation while translating LinkedIn articles written by various worldknown professionals into Lithuanian. A pitfall is understood here as a likely mistake or a translation problem; that is, any word, phrase or structure that causes a certain degree of doubt about its proper correspondence in the target language. Methodology. The mistakes made by students while translating 8 LinkedIn articles have been classified depending on their type: inaccurate wording, superfluous information, missing information, word order, punctuation, spelling, irregular lexical units and structures, and mistranslations. Several examples of each mistake have been selected and analysed. Analysis of each sample concludes with a discussion of alternative translation versions and suggestions for improvement of the translation based on translation strategies. Findings. The research revealed that the most significant pitfall is inaccurate wording; superfluous information comes next followed by punctuation mistakes. However, the most dangerous are mistranslations and irregular lexical units and structures left in translations, which prove that the translator failed to understand the information provided or lacks linguistic competence. The findings of the research suggest that translation practice classes should be transformed into a translation-learning instrument for students to acquire translation and target language competence and the skills needed to produce acceptable target language texts.